Investigation on mechanical properties and corrosion behavior of rubber for packer in CO2-H2S gas well. (June 2021) - Dong, Baojun; Liu, Wei; Cheng, Lin; Gong, Jindong; Wang, Yabin; Gao, Yancai; Dong, Shexia; Zhao, Yonggang; Fan, Yueming; Zhang, Tianyi; Chen, Longjun
Highlights: Mechanical properties and corrosion of rubbers for packer are investigated in CO2 -H2 S environment. Rubber corrosion mechanism has been analyzed. HNBR rubber should be carefully considered in CO2 -H2 S gas wells. Abstract: The rubber materials used in the packer play a key role to ensure the operation safety of oil and gas wells. Hence, it is of great significance to study the corrosion behavior of rubber materials in the packer under the CO2 -H2 S coexistence environment. In this study, the corrosion behavior of AFLAS, FKM and HNBR rubber under the CO2 -H2 S coexistence environment was observed by using a high-temperature and high-pressure autoclave. The experiment investigated mass growth rate, volume growth rate and mechanical properties of the samples. Based on EDS results and tensile fracture morphology, the corrosion mechanism of the three types of rubbers exposed to CO2 -H2 S environment was concluded. The results indicate that the mass and volume growth rate of AFLAS rubber is close to FKM, and the growth is at a rather low rate. By contrast, sharp increases both in mass and volume of HNBR rubber are clear to be seen. The effect of corrosion on the mechanical properties of AFLAS and FKM rubber is not evident, but the effect on HNBR is very significant. FKM rubber possesses properties of good corrosion and aging resistance, AFLAS following it, and HNBR has the worst corrosion and aging resistance capability under the CO2 -H2 S corrosive environment. Therefore, the use of HNBR rubber as packer material should be carefully considered in CO2 -H2 S gas wells.